2019
DOI: 10.1029/2019gl082405
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic Ice‐Rafting, Ocean and Atmospheric Circulation During the Holocene: Insights From Western Mediterranean Speleothems

Abstract: In this study, we present a Holocene rainfall index based on three high‐resolution speleothem records from the Western Mediterranean, a region under the influence of the westerly winds belt modulated by the North Atlantic Oscillation (NAO). On centennial to millennial timescales, we show that the North Atlantic ice‐rafting events were likely associated with negative NAO‐like conditions during the Early Holocene and the Late Holocene. However, our data reveal that this is not clearly the case for the mid‐Holoce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 72 publications
(119 reference statements)
4
52
0
Order By: Relevance
“…Repschläger et al, 2017), this would have also impacted the state of the NAO (e.g. Ait Brahim et al, 2019; Wassenburg et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repschläger et al, 2017), this would have also impacted the state of the NAO (e.g. Ait Brahim et al, 2019; Wassenburg et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Repschläger et al, 2017), this would have also impacted the state of the NAO (e.g. Ait Brahim et al, 2019;Wassenburg et al, 2016). Over orbital and millennial time scales, hydroclimate in westcentral Portugal has generally tracked North Atlantic SST variability (Sánchez Goñi et al, 2008Goñi et al, , 2013Goñi et al, , 2016, and these changes have been preserved within BG stalagmites (Denniston et al, 2018) with warmer (cooler) Atlantic SSTs corresponding to more humid (drier) conditions at BG.…”
Section: Millennial-scale Hydroclimate Variability During the Holocenmentioning
confidence: 99%
“…The stable isotope subsamples from WIN1 and WIN2 were drilled along the stalagmites growth axes using a hand drill with a spatial resolution of 1 mm. Isotope-Ratio Mass Spectrometry (Wassenburg et al, 2016) and Chaara cave (Ait Brahim, Wassenburg, et al, 2019) (blue dot), and other proxy sites (black circles) are shown in the map: 3 = OCE437-7-GC27 and 5 = OC437-07-GC37 (Tierney et al, 2017); 4 = GeoB 6007 (Kuhlmann et al, 2004) and GeoB 6007-2 (Holz et al, 2007); and 6 = ODP Site 1002 (Haug et al, 2001). Westerly jet stream (light blue arrow), ITCZ (gray dashed line), and typical positions of the Icelandic Low (IL) (black circle) and the Azores High (AH) (brown circle) are also shown in the map.…”
Section: Calcite Stable Isotope Analysismentioning
confidence: 99%
“…However, in contrast to the aforementioned monsoonal signal in SW Moroccan speleothems during the mid-Holocene, a completely different climate pattern was observed in speleothem records from N Morocco (Figure 3). Based on speleothem δ 18 O records from N Morocco (~34°N) and a compilation of climate records, there is evidence that positive NAO-like conditions prevailed during the mid-Holocene, whereas the early Holocene was characterized by relatively negative NAO-like conditions on multimillennial time scales (Ait Brahim, Wassenburg, et al, 2019). However, our data show that the speleothem δ 18 O values dropped to values as low as −8.5‰ in SW Morocco, which together with other hydroclimate records, suggest enhanced rainfall amount in SW Morocco during the AHP.…”
Section: The Wasm Belt Did Not Reach~34°n During the Ahpmentioning
confidence: 99%
See 1 more Smart Citation